PENGAWASAN POKDARWIS DI OBJEK WISATA DANAU MENDUYAN KABUPATEN INDRAGIRI HULU - Rani, Shinta Rizhkivia; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Indragiri Hulu Regency has a lot of potential in terms of various tourist attractions. Its development is inseparable from the role of the community and local government who are aware of the opportunities in the tourism sector to advance the welfare of the surrounding community. The sustainability of tourism will be maintained if there is supervision over the management and development of tourist attractions. The goal of this research is to determine the supervision of tourism awareness groups at the Lake Menduyan tourism objects. This study used descriptive qualitative method. Data was collected through direct observation in the field, interviews and documentation. The research results found that supervision standards at the Lake Menduyan tourism object were carried out by the regional government assisted by the Pokdarwis based on the conditions of Lake Menduyan, assessment actions are carried out on cleaning officers and Pokdarwis. Then, corrective action was taken through warnings delivered by the regional government for the deviations that occured. Keywords : Supervision, Pokdarwis, Danau Menduyan.